Endocervical adenocarcinoma of the gastric type: a case report and literature review - Yiting Yang; Xi Zhu; Yayan Zhou; Zihuang Li; Jingqing Liu; Minjie Fang (Frontiers in Oncology)
Gastric-type endocervical adenocarcinoma (G-EAC) is the most common type of non-human papillomavirus (HPV)-related cervical cancer. Specifically, G-EAC is highly malignant, has a poor prognosis, and is often missed or misdiagnosed, underscoring the need for caution. Herein, we report a case of a patient with G-EAC who underwent surgery, postoperative chemoradiotherapy, targeted therapy, and immunotherapy. Clinical symptoms such as vaginal aqueous secretion and elevated serum carbohydrate antigen-19-9 (CA19-9) levels may aid in diagnosing G-EAC. Of note, in PD-1-negative G-EAC patients, immunotherapy could offer potential benefits. Raising awareness and vigilance regarding this disease, along with developing highly specific antibodies for its early diagnosis, is crucial for improving patient outcomes.